Application of MXene in the diagnosis and treatment of breast cancer: A critical overview - Ranjbari, Sara; Darroudi, Mahdieh; Hatamluyi, Behnaz; Arefinia, Reza; Aghaee-Bakhtiari, Seyed Hamid; Rezayi, Majid; Khazaei, Majid (Frontiers in Bioengineering and Biotechnology, 2022)
Breast cancer is the second most common cancer worldwide. Prognosis and timely treatment can reduce the illness or improve it. The use of nanomaterials leads to timely diagnosis and effective treatment. MXenes are a 2D material with a unique composition of attributes, containing significant electrical conductance, high optical characteristics, mechanical consistency, and excellent optical properties. Current advances and insights show that MXene is far more promising in biotechnology applications than current nanobiotechnology systems. MXenes have various applications in biotechnology and biomedicine such as drug delivery/loading, biosensor, cancer treatment, and bioimaging programs due to their high surface area, excellent biocompatibility, and physicochemical properties. Surface modifications MXenes are not only biocompatible but also have multifunctional properties, such as aiming ligands for preferential agglomeration at the tumor sites for photothermal treatment. Studies have shown that these nanostructures, detection, and breast cancer therapy are more acceptable than present nanosystems in in-vivo and in-vitro. This review article aims to investigate the structure of MXene, various methods of its synthesis, and its application to cancer diagnosis, cytotoxicity, biodegradability, and cancer treatment by the photothermal process (in-vivo and in-vitro).